DESCRIPTION OF SEXUALITY IN MARRIED WOMEN AT PMB RATNA MIDWIFE HOUSE, SUKOHARJO CITY - Kumalasari, Ratna Dewi; Issabella, Chentia Misse; Purnamasari, Indah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2024)
Unfulfilled sexuality can have a negative impact on married couples, both affecting their physical, psychological and domestic health. Physically, women often feel pain, pain and discomfort during sexual intercourse. Emotionally, a person who does not meet his sexual needs will easily get emotional and feel unhappy with his partner and household. Unfulfilled sexuality can also affect the communication of married couples and often leads to poor treatment, disputes, domestic violence in couples and even divorce. Sexuality problems such as discomfort, pain and other complaints felt during sexual intercourse are often not revealed because of the fear of talking about them and the taboo of discussing them with others.Keywords : Female sexual function; women with married status